PELAKSANAAN PASAL 53 UNDANG-UNDANG NOMOR 22 TAHUN 2001 TENTANG MINYAK DAN GAS BUMI TERHADAP PENIMBUNAN BAHAN BAKAR MINYAK DI KOTA BATAM - Ma'arif, Husni; Zulkifli, Zulkifli (SCIENTIA JOURNAL, 2021)
Petroleum as a strategic natural resource contained in the indonesian mining jurisdiction is and has become an asset of national wealth that has been controlled by the State. This research aims to explain about the implementation of article 53 of Law No. 22 of 2001 on Oil and Gas Against The Storage of Fuel Oil In Batam city and how law enforcement by investigators against the perpetrators of criminal fuel hoarding in the city of Batam. This study uses empirical legal research. Data collection techniques are conducted through interviews. The data sources used are primary and secondary legal materials. Based on the results of research and discussion in the conclusion that the implementation of article 53 of Law No. 22 of 2001 on Oil and Gas against the stockpiling of fuel oil in the city of Batam is carried out with 3 (three) direct efforts from the police in minimizing the crime of fuel hoarding berusbsidi. The efforts intended are pre-emptive efforts, preventive efforts, and repressive efforts.